2018
DOI: 10.4103/ijmpo.ijmpo_70_17
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Differentiated Thyroid Carcinoma Risk Factor For Analysis For Disease Free Survival

Abstract: Context: The context of this study was epidemiology pediatric thyroid cancer in Bandung, Indonesia. Aims: The aim of this study is to evaluate clinical characteristics and outcome between children and young adult patients with differentiated thyroid cancer (DTC) treated in our hospital. Settings and Design: This was a cohort retrospective study. Materials and Methods: The medical records of 144 patients with DTC who underwent thyroid surgery followed by radioio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…All of them had a tumor size found an increased rate of recurrence in patients with lymph node metastasis. 22,23 Similar to these studies, lymph node metastasis was found to be significantly correlating with recurrence in univariate analysis and remained marginally significant in multivariate analysis as well.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…All of them had a tumor size found an increased rate of recurrence in patients with lymph node metastasis. 22,23 Similar to these studies, lymph node metastasis was found to be significantly correlating with recurrence in univariate analysis and remained marginally significant in multivariate analysis as well.…”
Section: Discussionsupporting
confidence: 77%
“…RAI ( 131 I), due to its ability to ablate normal remnant thyroid tissue and to treat iodine‐avid metastatic disease, has been used as an adjunct to surgical therapy. Radioablation is a frequently used modality of treatment used in 59–92% of reported cohorts and 62% of our patients received this modality 10,22,23 . As there are no uniform guidelines regarding the dose of RAI in children, different institutes used different doses of RAI based on weight/age of the child, or radioiodine uptake in the thyroid bed.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Age, radiation exposure of the head and neck region, family history, and environmental exposure are risk factors for thyroid malignancy [5,6]. e mortality rate of thyroid malignancy in children is usually <10%, but the recurrence rate is higher in children who are diagnosed when younger than 15 years with clinical presentation usually more severe than in adults [2,7]. yroid malignancy in younger patients has different characteristics than in adults in terms of clinical presentation, pathogenesis, and outcome owing to its biologic and molecular differences [7].…”
Section: Introductionmentioning
confidence: 99%
“…e mortality rate of thyroid malignancy in children is usually <10%, but the recurrence rate is higher in children who are diagnosed when younger than 15 years with clinical presentation usually more severe than in adults [2,7]. yroid malignancy in younger patients has different characteristics than in adults in terms of clinical presentation, pathogenesis, and outcome owing to its biologic and molecular differences [7]. Young patients with thyroid malignancy commonly do not show signs and symptoms but are diagnosed with malignant disease rather suddenly; therefore, it is often known as the silent killer [6].…”
Section: Introductionmentioning
confidence: 99%